A stochastic model for the utility of income - John K. Dagsvik; Steinar Strøm; Zhiyang Jia (University of Oslo, Department of Economics, 2003)
In this paper we propose a particular approach to measuring utility of income. To this end we develop a theoretical framework that restricts the class of admissible functional forms and distributions of the random components of the model. The theoretical approach is based on ideas and principles that are used in modern psychophysical research and theories of probabilistic choice.The empirical part of the paper is based on “Stated Preference” data (SPD). In the present context this means that individuals participating in a laboratory type of experiments are asked to rank order a set of hypothetical alternatives presented.
Keywords: B21; D19; 330; Utility of income; Random utility; Invariance principles; Nutzen; Einkommen; Random Walk